Formulation of Business Development Strategies in Gula Aren Temon SMEs in Pacitan District - Royyaa Shobaah; Heru Irianto; Kusnandar Kusnandar (Green Publisher Indonesia, 2023)
The development company is one of the important factors underlying the creation of a successful business so that it can maintain its productivity in the long term. Likewise, MSMEs need to design a business strategy to support the progress of their business during increasingly competitive business competition. This study aims to identify business implementation, analyze business potential, and formulate strategic priorities in Gula Aren Temon SMEs. The research method used is a qualitative method with analytical tools in the form of BMC, VRIO, SWOT, and QSPM. The results of the study show that the nine building blocks of the BMC analysis describe the interrelated elements of Gula Aren Temon SME’s business implementation. The VRIO analysis results show that most of the resources owned by the business are at competitive parity. The results of the SWOT Analysis show that there are nine alternative strategies, while the priority chosen strategy to implement is to maximize the quality of service and products to maintain relationships with consumers and other partners. The strategy was chosen based on the highest TAS score, namely 6,280.